PEMBANGUNAN APLIKASI PERSEDIAAN BERAS BULOG PADA KANTOR LURAH PARAK LAWEH PULAU AIE NAN XX KOTA PADANG - Anisya (ITP Press, 2013)
In Parak Laweh Pulau Aie Nan XX has activity what is distribution government rice for peoples who depend of in this activity . Purpose of this researches are help out especially Aisyiyah’s Hospital in care-inpatient e-data processing with building a information system using PHP programming language and MySQL Databases.